Reconstruction of inclined air showers detected with the Pierre Auger Observatory - Aab, A. (2014)
We describe the method devised to reconstruct inclined cosmic-ray air showers with zenith angles greater than 60 detected with the surface array of the Pierre Auger Observatory. The measured signals at the ground level are tted to muon density distributions predicted with atmospheric cascade models to obtain the relative shower size as an overall normalization parameter. The method is evaluated using simulated showers to test its performance. The energy of the cosmic rays is calibrated using a sub-sample of events reconstructed with both the fuorescence and surface array techniques. The reconstruction method described here provides the basis of complementary analyses including an independent measurement of the energy spectrum of ultra-high energy cosmic rays using very inclined events collected by the Pierre Auger Observatory.